Plastic Hinge Relocation in Reinforced Concrete Frames as a Method of Improving Post-earthquake Fire Resistance. (June 2015) - Behnam, Behrouz; Lim, Pang Jen; Ronagh, Hamid R.
Abstract: Post-earthquake fire (PEF) presents a risky situation to buildings that have been partially damaged in a prior earthquake, particularly in urban areas. As most standards ignore the possibility of fire after earthquake, buildings are not adequately designed for that possibility and thus PEF is a high-risk load needed to be scrutinized further, codified and become part of a routine design. An investigation based on sequential analysis inspired by FEMA356 is performed here on a two story RC frame, at the Life Safety performance level and designed to the ACI 318-08 code, after it has been subjected to a spectral PGA of 0.35 g. The results show that structures previously damaged by the earthquake and exposed to PEF are considerably more vulnerable than the structures, which have not been damaged previously. A method of strengthening using Carbon Fiber Reinforced Polymer (CFRP) wraps is introduced in order to relocate plastic hinges away from the column faces towards the beams. This method increases the structural load carrying capacity, and thus reduces the potential damage from a potential earthquake, improving the fire resistance. The results show a considerable improvement in the PEF resistance of the frame.